Efektivitas Media Pembelajaran Video dan Media Demonstrasi Untuk Meningkatkan Kompetensi Praktik Pendidikan Kesehatan di STIKes Karsa Husada Garut - dede Suharta (STIKes Karsa Husada Garut, 2016)
Low ability students in educational practice kesehtaan allegedly besides the nature of abstract studies, as well as lectures is not supported by appropriate learning media. Through this research will study whether the use of media and instructional video demonstration can improve the competence of student health education practice STIKes Karsa Husada? The study was conducted using a quantitative approach with one-shot method of quasi-experimental design, research instruments used, namely observation guidelines. By using nonequivalent control group design (Sugiyono), a picture that health education practice teaching using instructional media and demonstration videos, can significantly improve the ability of students to learn the practice of STIKes Karsa Husada Garut. This means learning practices using pembelelajaran Media video and demonstration can improve student practice, better skills Preparation up to the documentation phase. Based on these results dirokemendasikan to the faculty, it would be better if the media are used instructional videos and demonstrations Those materials delivered another lecture. Because the use of instructional media, the students not only enthusiastic (motivated) interact in lectures but demonstrated the ability prektiknya increases. Because the medium of learning are manifold. Suggestions for further research can explore a variety of advantages and accuracy of each medium of learning from the aspects of the lecture material.